2017
DOI: 10.1037/abn0000311
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the idiographic dynamics of mood and anxiety via network analysis.

Abstract: Individual variation is increasingly recognized as important to psychopathology research. Concurrently, new methods of analysis based on network models are bringing new perspectives on mental (dys)function. This current work analyzed idiographic multivariate time series data using a novel network methodology that incorporates contemporaneous and lagged associations in mood and anxiety symptomatology. Data were taken from 40 individuals with generalized anxiety disorder (GAD), major depressive disorder (MDD), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
259
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 303 publications
(296 citation statements)
references
References 57 publications
9
259
0
2
Order By: Relevance
“…Out of the 9 studies that focused on comorbidity with depressive symptoms, some have analyzed comorbid MDD and GAD [66-69]. All of them found a highly connected network in which no symptom remained isolated from the others.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the 9 studies that focused on comorbidity with depressive symptoms, some have analyzed comorbid MDD and GAD [66-69]. All of them found a highly connected network in which no symptom remained isolated from the others.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding centrality, studies have reached different conclusions. While 1 study found that “worry” and “sad mood,” the main diagnostic criteria for GAD and MDD, respectively, were the most central in a cross-sectional network [68], another study found that these symptoms were the least central in a temporal network [69]. However, both studies pointed out “anhedonia” and “guilt” as highly central in their comorbid networks.…”
Section: Resultsmentioning
confidence: 99%
“…Fisher et al. (2017) further argued that, through leveraging the rich individual‐level information these methods provide, idiographic methods can also be used to meaningfully transform the field's approach to the classification of psychopathology. Idiographic network models are especially well suited for these tasks.…”
mentioning
confidence: 99%
“…23,24 An example of an idiographic network is illustrated in a hypothetical case presented below ( Figure 1). This approach is unlikely to offer a useful alternative classification system to the DSM or the ICD any time soon.…”
Section: Perspective On Psychopathologymentioning
confidence: 99%